Predictors of late complications after coronary artery bypass grafting in patients with stable coronary heart disease - O.J. Zharinov; К.O. Mikhaliev; O.A. Yepanchintseva; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія, 2018)
The aim – to determine factors that may influence the occurrence of late complications after coronary artery bypass surgery (CABG) in patients with stable coronary heart disease. Materials and methods. In a single-center study, data from clinical and instrumental examinations of 155 patients with stable coronary heart disease consecutively selected for isolated CABG were analyzed. The duration of the follow-up period was 12 months after surgery. In general, 29 late complications (3 cases of heart failure, 3 – first diagnosed atrial fibrillation (AF), 4 – acute coronary syndrome, 11 – left ventricular ejection fraction (LV EF) relative decrease more than 10 %, 2 – formation of atrial fibrillation permanent form, 2 – acute myocardial infarction and 4 deaths) were diagnosed in 24 patients. Groups of patients with and without complications were compared according to demographic parameters, risk factors, concomitant diseases, laboratory parameters, features of the CABG operation and postoperative therapy. Results. In unifactor analysis the features of patients with complications during 1-year observation, were earlier presence of AF, lower glomerular filtration rate (GFR) (median (quartile) 55 (44–68) versus 61 (52–74) ml/(min · 1,73 m2); p = 0.060); higher left atrium size (4.4 (4.3–4.9) cm vs. 4.3 (4.0–4.5) cm; p = 0.004); lower LV EF (47 (37–56) % vs. 53 (45–58) %; p = 0.033); higher end-diastolic volume index (70.4 (58.7–84.8) сm3/m2 vs. 59.1 (51.2–70.8) сm3/m2; p = 0.004), post-operative use of aldosterone antagonists (p = 0.051) and loop diuretics (p = 0.007), absence of statin therapy (p < 0.001). According to the multivariate analysis, the independent predictors of late complications after CABG were the worst GFR at discharge (OR 1.366 (95 % CI 1.007–1.853), p = 0.045), postoperative use of loop diuretics (OR 2.186 (95 % CI 1.187–4.024), p = 0.012) and the absence of postoperative statin therapy (OR 6,236 (95 % CI 2.313–16.809), p < 0.001). Conclusions. The majority of registered late complications after CABG were the cases of left ventricular pump function worsening, the appearance and progression of atrial fibrillation and/or heart failure. An independent association of late complications occurrence with renal function decrease, loop diuretics treatment and absence of long-term statin therapy should be taken into account for prescription, control and correction of treatment during late postsurgery period.